THE CRISIS OF MUSLIM FAMILY RESILIENCE IN THE AL-QURAN PERSPECTIVE: SOLUTIONS AND STRATEGIES IN THE DIGITAL ERA - Nurafni; Hidayatullah Ismail; Ilyas Husti (RADJA PUBLIKA, 2025)
Muslim family resilienceis an essential element in maintaining the sustainability of a based societyIslamic values. In the midst of cultural and technological transformation, the family is the first fortress for its members to maintain noble morals, faith and spiritual values ​​taught inAl-Qur'an. The importance of this resilience is not only to face the challenges of the times, but also to build a generation that is steadfast in faith and contributes positively to the people. The Koran positions the family as an institution that must maintain its strength through love, responsibility and harmony between members. This resilience allows families to live life with the principles of justice and togetherness even though they are faced with various tests, including influencedigital age. By making the family the center of character formation and religious learning, Islamic values ​​can continue to be passed on with full vitality from one generation to the next.